USING NEURAL NETWORK TECHNOLOGIES IN TEACHING ENGLISH - Shavkat Ibragimov; Rezhepkhon Ravshanbekova (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This paper investigates the effectiveness of neural network technologies in teaching English to university students. A pedagogical experiment was conducted with a control group (n = 62) and an experimental group (n = 58) of first-year students. The experimental group studied using an integrated neural network educational system comprising an NLP module, an adaptive task planner, and a personalised feedback subsystem. After a 12-week period, the experimental group showed statistically significant improvements across all five measured competences: vocabulary, grammar, reading, listening, and writing (p < 0.01). The mean aggregate score increased from 50.6% to 73.2% (+44.7%), whereas the control group improved from 50.2% to 61.2% (+21.9%). The findings confirm the promise of neural network tools in higher-education language instruction.